(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
In a recent publication by Modi et al. [Jour. of At. Mol. Cond. and Nano Phys. 2 (2015), 41], cross sections for the scattering of electrons and positrons from hydrogen atoms and molecules have been calculated in the Debye plasma, using the Born approximation. Using the exchange approximation for the scattering, it is shown here that at low energies they have considered, the cross sections for the triplet and the singlet states are not equal. Moreover, they differ considerably from their results.